2008
DOI: 10.1177/1470595808091790
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Individual Collectivism on Commitment and Its Influence on Organizational Citizenship Behaviour and Turnover in Three Countries

Abstract: Increasing globalization and rising markets in Eastern Europe and Asia have led to a growing interest in issues of cross cultural management. In western culture, high correlations have been found between leadership, commitment, turnover and performance. In this study we examined the influence of cultural differences on employees' commitment and its impact on relevant outcomes at the individual and the country level. Collectivism was directly measured at the individual level. Organizational citizenship behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 40 publications
(74 reference statements)
4
86
0
1
Order By: Relevance
“…In such contexts, transformational leaders may be expected to create more positive outcomes. Indeed, previous research claims that TL tends to emerge and be more effective in collectivist environments and for collectivists (Bass, 1995;Felfe, Yan, & Six, 2008, Jung, Bass, & Sosik, 1995Walumbwa, Lawler, & Avolio, 2007). Cultural values in such contexts seem to be more in line with those leaders' emphases on a collective mission and collective goals and responsibilities (Jung & Yammarino, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…In such contexts, transformational leaders may be expected to create more positive outcomes. Indeed, previous research claims that TL tends to emerge and be more effective in collectivist environments and for collectivists (Bass, 1995;Felfe, Yan, & Six, 2008, Jung, Bass, & Sosik, 1995Walumbwa, Lawler, & Avolio, 2007). Cultural values in such contexts seem to be more in line with those leaders' emphases on a collective mission and collective goals and responsibilities (Jung & Yammarino, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Some authors have argued that commitment matters more for outcomes in collectivist cultures than it does in individualist cultures. For example, Lee et al (2001) reported higher correlations between NC and intention to leave for samples in collectivist cultures than for North American ones, and Felfe, Yan, and Six (2008) recently found stronger effects of AC and NC on turnover intention in China and Romania compared to Germany. This result is not supported by Glazer and Beehr (2005), who deemed the effects of AC and CC on turnover intention to be largely equivalent in Hungary, Italy, the United Kingdom, and the United States.…”
Section: Jp As Outcomementioning
confidence: 99%
“…Specifically, research has found no significant difference between the effects of affective and normative commitment on organizational outcomes (Felfe et al, 2008). Consequently, normative commitment is often excluded from studies; affective and continuance commitment being more commonly used forms (Dunhab et al, 1994;Gautam et al, 2004).…”
Section: Commitmentmentioning
confidence: 99%